The Effect of Coil and Spark Plug Variation on Emission, Power and Torque on Vixion 150 - Satrio, Hutomo Jiwo; Pramanda, Wibi (Program Studi Teknik Mesin Universitas Pamulang, 2024)
The development of technology in vehicles continues to be developed to meet human needs and be environmentally friendly. One technology that is still being developed is the use of spark plugs and coils. The function of spark plugs in motorized vehicles is to spark sparks caused by the electric voltage generated by the coil. Various kinds of coil produce different high voltage. This research uses a Yamaha Vixion 150 CC, 1 cylinder, four-stroke motorcycle. The research was conducted by providing spark plug and coil variations including standard U24ESR-N (Denso) spark plugs, 0.4mm Iridium spark plugs, and Brisk Silver spark plugs. Coil variations were also given including 3C1 H2310 spark plugs and Uma Racing spark plugs. The data taken includes a comparison of emissions produced, torque, and power. The highest power at RPM 8500 was generated by the U24ESR-N spark plug (Denso) with the use of the Uma Racing coil type of 8.69 kW. Spark plug and coil variations will also determine torque. The highest test on the use of Uma Racing coil and Brisk Silver spark plug at 6500 RPM engine speed produces a value of 9.35 Nm. The results also show changes in emissions produced such as CO2, CO, HC, and O2 emissions. The use of 0.4mm Iridium spark plugs with 3C1 H2310 coil and Brisk Silver spark plugs with 3C1 H2310 produces high voltage resulting in higher CO and HC gas production